Aberrant COL11A1 splicing causes prelingual autosomal dominant nonsyndromic hearing loss in the DFNA37 locus. Issue 1 (11th November 2020) - Rad, Aboulfazl; Schade‐Mann, Thore; Gamerdinger, Philipp; Yanus, Grigoriy A.; Schulte, Björn; Müller, Marcus; Imyanitov, Evgeny N.; Biskup, Saskia; Löwenheim, Hubert; Tropitzsch, Anke; Vona, Barbara
Abstract: Alpha‐chain collagen molecules encoded by genes that include COL11A1 are essential for skeletal, ocular, and auditory function. COL11A1 variants have been reported in syndromes involving these organ systems. However, a description of the complete clinical spectrum is lacking, as evidenced by a recent association of autosomal dominant nonsyndromic hearing loss due to a splice‐altering variant in COL11A1, mapping the DFNA37 locus. Here, we describe two German families presenting prelingual autosomal dominant nonsyndromic hearing loss with novel COL11A1 heterozygous splice‐altering variants (c.652‐1G>C and c.4338+2T>C) that were molecularly characterized. Interestingly, the c.652‐1G>C variant affects the same intron 4 canonical splice site originally reported in the DFNA37 family (c.652‐2A>C) but elicits a different splicing outcome. Furthermore, the c.4338+2T>C variant originated de novo. We provide clinical and molecular genetic evidence to unambiguously confirm that COL11A1 splice‐altering variants cause DFNA37 hearing loss and affirm that COL11A1 be included in the genetic testing of patients with nonsyndromic deafness. Abstract : We describe two German families presenting prelingual autosomal dominant non‐syndromic hearing loss with novel COL11A1 heterozygous splice‐altering variants c.652‐1G>C and c.4338+2T>C that were molecularly characterized. Interestingly, the c.652‐1G>C variant affects the same intron 4 canonical splice site originally reported in the DFNA37 family (c.652‐2A>C) but elicits a different splicing outcome. Furthermore, the c.4338+2T>C variant originated de novo. We provide clinical and molecular genetic evidence to unambiguously confirm that COL11A1 splice‐altering variants cause DFNA37 hearing loss and affirm that COL11A1 be included in genetic testing of patients with nonsyndromic deafness.